Single-incision laparoscopic splenectomy with innovative gastric traction suture - Srikanth, G (Medknow Publications, 2011)
Laparoscopic splenectomy is now the gold standard for patients with idiopathic thrombocytopenic purpura (ITP) undergoing splenectomy. There are a few reports in literature on single-incision laparoscopic (SIL) splenectomy. Herein, we describe a patient undergoing SIL splenectomy for ITP without the use of a disposable port device. We report a 20-year-old female patient with steroid-refractory ITP having a platelet count of 14,000/cmm who underwent a SIL splenectomy. Dissection was facilitated by the use of a single articulating grasper and a gastric traction suture and splenic vessels were secured at the hilum with an endo-GIA stapler. She made an uneventful postoperative recovery and was discharged on the second postoperative day. She is doing well with no visible scar at 8-month follow-up.